Antitumor effect of a transducible fusogenic peptide releasing multiple proapoptotic peptides by caspase-3 - Kwon, Mi-Kyung; Nam, Ju-Ock; Park, Rang-Woon; Lee, Byung-Heon; Park, Jae-Yong; Byun, Young-Ro; Kim, Sang-Yoon; Kwon, Ick-Chan; Kim, In-San (AMER ASSOC CANCER RESEARCH, 2008)
We have designed a novel peptide, TK3, composed of three functional domains, a protein transduction domain, a TAT followed by three tandem repeats of a proapoptotic peptide, and a caspase-3 cleavage site, (KLAKLAK)(2)-DEVD. TK3 was able to transduce into cells and then activate caspase-3, which in turn cleaved TO to release additional (KLAKLAK)(2) peptides. (KLAKLAK)(2) was well transduced by TAT into tumor cells and was able to induce apoptosis in vitro and in vivo. TK3 also induced apoptosis and inhibited angiogenesis in endothelial cells. Further, direct injection of TK3 into established B16F10 melanoma tumors in C57BL/6 mice resulted in almost complete inhibition of the tumor growth. These results suggest that TK3 could be beneficial for the treatment of accessible tumors and used as an adjuvant for cancer therapy.
Keywords: VIVO PROTEIN TRANSDUCTION; IN-VIVO; INTRACELLULAR DELIVERY; TUMOR VASCULATURE; TAT PROTEIN; MOUSE; CELLS; INHIBITION; BETA-IG-H3; INTEGRIN